Formation of (Cu)(n) & (Cu2O)(n) nanostructures with the stability of their clusters - Iskakova, K.; Akhmaltdinov, R.; Kuketaev, T. (Amer inst mathematical sciences-aims, 2018)
We investigated the electronic structure and the properties of cupper (Cu) and compound semiconductor (Cu2O) by with the help of computer simulation of the programs developed by us and obtaining various morphologies and properties of Cu nanostructures by the method of template synthesis, including the study of the direction of formation processes and the practical application of ion tracks. In calculations of the computer simulation programs developed by us, the general and area-predicted density of states and the band dispersion of optimized crystal structures with different structural units (Cu)n (n = 6, 12) and (Cu2O)n (n = 16, 23) were described. Accordingly, this leads to the prediction that (Cu)n at n = 12 and (Cu2O)n at n = 23 take a high electron density, and that the energy maximum points arise where there is a low electron density and, conversely, for electron energy minima, the electron density is high. The maxima of the level energy n = 2 for (Cu)n and (Cu2O)n, the corresponding electron densities also reached their maximums, but these values of the metallic and semiconductor junctions, respectively, were sharply different in value when compared with each other. This indicates that the changes in the electronic states were due mainly to the replacement of the oxygen atom and subsequent modification of the crystalline field.
Keywords: BCC structure; FCC structure; clusters; direct space; inverse space; lattice